PENGARUH ROA DAN ROE TERHADAP PERTUMBUHAN LABA PADA SEKTOR PERBANKAN DI BEI - Pasaribu, Novitauli Lamtiur (Fakultas Ekonomi Prodi Akuntansi, 2023)
This discussion aims to find out whether ROA and ROE affect profit growth in the banking sector, which was recorded on the IDX for the 2019-20211 period with a total population of 47 industries. The purposive sampling method determines the sample; the whole model is 28 companies × three years = 84 total samples. Two types of data are used, namely quantitative data and secondary data. The data collection process uses the documentation method available on the IDX website. Simultaneous and partial hypothesis testing was used to test this hypothesis. The regression model used is a multiple linear regression analysis. According to the test results, ROA and ROE have a positive but insignificant effect on profit growth.